Treatment of paediatric malaria during a period of drug transition to artemether-lumefantrine in Zambia: cross sectional study. - Zurovac, D; Ndhlovu, M; Rowe, A; Hamer, D; Thea, D; Snow, R (2005)
OBJECTIVE: To evaluate treatment practices for uncomplicated malaria after the policy change from chloroquine to sulfadoxine-pyrimethamine and to artemether-lumefantrine in Zambia. DESIGN: Cross sectional survey. SETTING: Outpatient departments of all government and mission facilities in four districts in Zambia. PARTICIPANTS: 944 children with uncomplicated malaria seen by 103 health workers at 94 health facilities. MAIN OUTCOME MEASURES: Antimalarial prescriptions in accordance with national guidelines and influence of factors on health workers' decision to prescribe artemether-lumefantrine. RESULTS: Artemether-lumefantrine, sulfadoxine-pyrimethamine, and chloroquine were available, respectively, at 48 (51%), 94 (100%), and 71 (76%) of the 94 facilities. Of 944 children with uncomplicated malaria, only one child (0.1%) received chloroquine. Among children weighing less than 10 kg, sulfadoxine-pyrimethamine was commonly prescribed in accordance with guidelines (439/550, 79.8%). Among the children weighing 10 kg or more, sulfadoxine-pyrimethamine was commonly prescribed (266/394, 68%), whereas recommended artemether-lumefantrine was prescribed for only 42/394 (11%) children. Among children weighing 10 kg or more seen at facilities where artemether-lumefantrine was available, the same pattern was observed: artemether-lumefantrine was prescribed for only 42/192 (22%) children and sulfadoxine-pyrimethamine remained the drug of choice (103/192, 54%). Programmatic activities such as in-service training and provision of job aids did not seem to influence the prescribing of artemether with lumefantrine. CONCLUSION: Although the use of chloroquine for uncomplicated malaria was successfully discontinued in Zambia, the change of drug policy towards artemether-lumefantrine does not necessarily translate into adequate use of this drug at the point of care.